2006
DOI: 10.1080/02673030500484935
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Policy Making: Some Reflections on the Application of Systematic Reviews to Housing Research

Abstract: The recent turn towards evidence-based or evidence-informed policy making has generated interest in systematic literature review techniques. Systematic reviewing is increasingly being adopted to address questions in complex social policy areas, but the methodological development lags behind. Drawing on the experience of undertaking three systematic reviews of housing related topics, as part of a project designed to empirically test the transfer of systematic review methods to social policy and social care, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
(25 reference statements)
0
24
0
Order By: Relevance
“…The process is both systematic and documented such that, if repeated, similar results and conclusions would be found, and thus reflects the replicability principle of the scientific method more broadly. The benefits of systematic literature reviews for decision makers and planners include: (a) less reliance on a single research study and the opportunity to view possibly divergent studies together, facilitating a comparison of the findings and providing a synthesis of the challenges and advantages of models, processes, or strategies from a variety of perspectives [14, 21, 22], and (b) time-savings since the underpinning of systematic literature reviews is the rigorous evaluation and synthesis of the findings reported in the literature making for easier access to evidence-based information [14, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…The process is both systematic and documented such that, if repeated, similar results and conclusions would be found, and thus reflects the replicability principle of the scientific method more broadly. The benefits of systematic literature reviews for decision makers and planners include: (a) less reliance on a single research study and the opportunity to view possibly divergent studies together, facilitating a comparison of the findings and providing a synthesis of the challenges and advantages of models, processes, or strategies from a variety of perspectives [14, 21, 22], and (b) time-savings since the underpinning of systematic literature reviews is the rigorous evaluation and synthesis of the findings reported in the literature making for easier access to evidence-based information [14, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Bambra (2005) highlights the difficulties inherent in attributing impact to specific policies (and thus their potential impact in other contexts) when the environment in which these policies are evaluated is already shaped by other policies that are themselves evolving. In a similar vein, Wallace et al (2006) point to the significant social and economic changes that can take place over time and which may confound external validity.…”
Section: Internal Versus External Validitymentioning
confidence: 94%
“…For example, when we are assessing the internal validity of comparative effectiveness studies, we intend to use a standard tool for assessing risk of bias and for other study types, such as process evaluations, we intend to assess them using a modified version of the Wallace et al . quality appraisal tool for qualitative studies [10]. For the purposes of transparency, we shall document our decisions about rigour (as appraised by the tools) and relevance (the contribution the piece makes to the review as a whole).…”
Section: Methodsmentioning
confidence: 99%